Challenging the Current Concept of Critical Glenoid Bone Loss in Shoulder Instability: Does the Size Measurement Really Tell It All?. Issue 3 (March 2019) - Moroder, Philipp; Damm, Philipp; Wierer, Guido; Böhm, Elisabeth; Minkus, Marvin; Plachel, Fabian; Märdian, Sven; Scheibel, Markus; Khatamirad, Mohammad
Background: Bone loss at the anterior glenoid rim is a main reason for failure of soft-tissue based surgical stabilization procedures in patients with anterior shoulder instability. Purpose: To evaluate the capability of conventional glenoid bone loss measurement techniques to provide an adequate estimation of the actual biomechanical effect of glenoid defects. Study Design: Descriptive laboratory study. Methods: Thirty consecutive patients with unilateral anterior shoulder instability and varying degrees of glenoid defect were included. Patient-specific computer tomography–based 3-dimensional shoulder models of the affected and unaffected sides were created. The bony shoulder stability ratio (SR) was determined in various potential dislocation directions with finite element analysis. Values obtained from conventional glenoid defect size measurement techniques (Pico and Sugaya) were correlated with the finite element analysis results. Additionally, a mathematical model was developed to theoretically analyze the correlation between glenoid defect size measurements and the SR. Results: The authors found substantial interindividual differences of the SR of the unaffected shoulders in all directions of measurement. Bone loss at the anterior glenoid rim significantly reduced the SR in the 2-o'clock ( P = .011), 3-o'clock ( P < .001), and 4-o'clock ( P < .001) directions referring to a right shoulder. The correlation between the defect size measurements and the SR for the 2-o'clock (rho = −0.522 and −0.580), 3-o'clock (rho = −0.597 and −0.580), and 4-o'clock (rho = −0.527 and −0.522) directions was statistically significant. However, it showed only moderate strength and was nonlinear as well as dependent on the inherent shape of the concavity. As shown by the mathematical model, bone loss has the most considerable effect at the edge of the glenoid rim, and an increasingly concave-shaped glenoid leads to an increase in loss of SR provoked by the same extent of bone loss. Conclusion: Current glenoid bone loss measurements are unable to provide an adequate estimation on the actual biomechanical effect of glenoid defects because (1) the relation between the glenoid defect size and its biomechanical effect is nonlinear and (2) patients with shoulder instability have constitutional biomechanically relevant glenoid concavity shape differences. Clinical Relevance: These findings challenge the current concept of setting a general threshold for critical glenoid bone loss, which requires bony reconstruction surgery.